Penerapan teori badan hukum dalam pelaksanaan akuisisi perseroan terbatas (Studi Putusan KPPU No. 06/KPPU-M/2024) - Dwi Aryanti Ramadhani; Sunandar Pramono; Army Setyo Wibowo; Wicipto Setiadi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
Acquisitions of limited-liability companies (Perseroan Terbatas, PT) in Indonesia continue to rise, yet not all of them generate maximum benefit for shareholders, creditors, employees, and the public. This study examines the application of legal entity theory at every stage of an acquisition—from the pre-acquisition phase, through the transaction itself, to the post-acquisition period—and analyses how the principle of “the greatest happiness for the greatest number” can be aligned with Indonesian positive law. KPPU Decision No. 06/KPPU-M/2024 affirms that every limited liability company (PT) is an independent legal subject, so the statutory notification of an acquisition must be filed by the PT that actually exceeds the concentration threshold. Using a qualitative method and a case-study approach, this article examines how the theory of legal entity is applied in the acquisition of PT Sumber Baru Hydropower by PT Tamaris Hidro. The findings are: (i) KPPU rejected the “single economic entity” doctrine and upheld the principle of legal-entity independence; (ii) procedural factors (wrong notifying party) obstructed economic utility, while the absence of a social-impact assessment hindered social utility. The article recommends integrating a “Joint Utility Plan” as a prerequisite for the conditional no-objection letter.